Penentuan kriteria derajat luka dalam visum et repertum dan analisis medikolegal pada korban kecelakaan lalu lintas - Satria Perwira (Universitas Syiah Kuala, 2022)
Background: A traffic accident is an unexpected and unintentional event involving a vehicle with or without other road users which causes human victims to suffer minor injuries, moderate injuries, and serious injuries.Case Presentation: A letter has been received for a request for Visum et Repertum (VeR) Luka from the Surabaya Police with a statement that the person is suspected to have suffered traffic accident injuries on Jalan Raya Medokan Sawah on September 21, 2021 at 10.00 WIB. General examination, wounds and support were carried out. The results of the examination and the conclusion of the degree of injury are then written into a VeR.Conclusion: VeR serves as legal evidence, as evidence for the detention of suspects, and as material for judge's consideration. The application of the degree of injury in the writing of the conclusion of the VeR does not mention the degree of injury, but the impact is stated as formulated in the criminal provisions in the Criminal Code or other laws.